Policy analysis the impact of GDP, the ratio of prices and exchange rates in neighboring countries on the development of agricultural exports - Babapour, Mojahed; Seyed nourani, Seyed mohamadreza; Ali Asghar Ebrahimi, (Technium Social Sciences Journal, 2021)
Today, due to international changes regarding the sharp decline in oil revenues, the negative impact of diseases such as Corona-virus on many parts of the country and international trade, change in patterns of development of national income is inevitable. In the current situation, changing the main variables of the country's development, the importance of exporting agricultural products to the national economy and the growth and development of the country is undeniable. Despite numerous studies that support the export of non-oil products for the growth of the country's exports, the effect of price ratios, exchange rates and the GDP of neighboring countries on the country's exports have not been studied. In this article, with the approach of econometric approach and using data panel method, the test of export of Iranian agricultural products to neighboring countries has been tested. According to the research findings, the effects of GDP on the export of Iran's agricultural products are positive and significant, and the effects of price-to-price ratios between Iran and neighboring countries, as well as the effects of exchange rate ratios between Iran and neighboring countries on Iran's agricultural exports, are negative and significant. Therefore, the increase in gross domestic product of neighboring countries increases the export of Iranian agricultural products to these countries and by increasing domestic prices compared to the prices of neighboring countries and increasing the domestic exchange rate compared to the exchange rate of neighboring countries reduces Iran's agricultural exports.